IMPLEMENTASI PLATFORM AS A SERVICE (PAAS) PADA DATABASE E-COMMERCE BERBASIS CLOUD COMPUTING - Wadly, Fachrid; Arpan; Muttaqin, Muhammad (CV. Hawari, 2023)
Business competition in the field of information technology continues to increase, one of the technologies itself is cloud computing. Cloud computing can be public or private. One type of cloud computing service used in this study is PaaS. The PaaS cloud computing service provides a platform that users can use to create applications. The Byna Cake shop is a shop that opens a cake business in Aceh, which is located on Pulau Tiga, Aceh, Tamiang. This shop sells various types of cakes which have been produced manually by themselves since 2021. The sales system uses WhatsApp and Instagram media and comes directly to the store, so this system is considered to be less effective and efficient. Therefore, an online sales system is needed, namely by building a web-based E-Commerce application. In implementing this web-based e-commerce application, the author utilizes cloud infrastructure as a cloud provider, namely Microsoft Azure. Computing service used in this research is CMS AbanteCart. Web-based e-commerce application at the Byna Cake store created by configuring a virtual machine to install CMS AbanteCart Packaged By Bitnami on the Microsoft Azure platform. The design used in creating web-based e-commerce applications at the Byna Cake store uses Use Cases and Class Diagrams.